The Moderating Effect of Psychological Contract Violation on the Relationship between Narcissism and Outcomes: An Application of Trait Activation Theory - Zagenczyk, Thomas J.; Smallfield, Jarvis; Scott, Kristin L.; Galloway, Bret; Purvis, Russell L. (Frontiers in Psychology, 2017)
We draw upon trait activation and psychological contracts theories to argue that narcissism is a personality trait that will manifest itself in the form of exit and neglect when employees experience psychological contract violation. In a sample of 262 employees from various organizations sampled at two points in time, we found that employees with high levels of narcissism and high levels of psychological contract violation tended to have higher levels of exit than did other employees. However, we did not find support for our prediction regarding neglect. Our results suggest that understanding the importance of narcissism at work may require consideration of the situation as opposed to broadly making assumptions based exclusively on this personality trait. Our research thus contributes to research on narcissism in the workplace, trait activation theory, and the role that individual differences play in shaping employee responses to psychological contract violation.